Performance Evaluation of IEEE 802.11 ac WPA2 Laboratory Links - Carvalho, José Pacheco de (2019)
The increasing importance of wireless communications, involving electronic devices, has been widely recognized. Performance is a fundamental issue, resulting in more reliable and efficient communications. Security is also crucially important. Laboratory measurements are presented about several performance aspects of Wi-Fi IEEE 802.11ac WPA2 point-topoint links. Our study contributes to performance evaluation of this technology under WPA2 encryption, using available equipments (Cisco 2702i access points and TP-Link AC1900 USB 3.0 adapters). New results are given from TCP and UDP experiments concerning TCP throughput versus TCP packet length, jitter and percentage datagram loss versus UDP datagram size. Comparisons are made to corresponding results for WPA2 802.11n. Conclusions are drawn about the comparative performance of the links.